Nox2 Deficiency Reduces Cartilage Damage and Ectopic Bone Formation in an Experimental Model for Osteoarthritis - Nik N. L. Kruisbergen; Irene Di Ceglie; Yvonne van Gemert; Birgitte Walgreen; Monique M. A. Helsen; Annet W. Slöetjes; Marije I. Koenders; Fons A. J. van de Loo; Johannes Roth; Thomas Vogl; Peter M. van der Kraan; Arjen B. Blom; et al. (MDPI AG, 2021)
Osteoarthritis (OA) is a destructive disease of the joint with age and obesity being its most important risk factors. Around 50% of OA patients suffer from inflammation of the synovial joint capsule, which is characterized by increased abundance and activation of synovial macrophages that produce reactive oxygen species (ROS) via NADPH-oxidase 2 (NOX2). Both ROS and high blood levels of low-density lipoprotein (LDL) are implicated in OA pathophysiology, which may interact to form oxidized LDL (oxLDL) and thereby promote disease. Therefore, targeting NOX2 could be a viable treatment strategy for OA. Collagenase-induced OA (CiOA) was used to compare pathology between wild-type (WT) and Nox2 knockout (Nox2−/−) C57Bl/6 mice. Mice were either fed a standard diet or Western diet (WD) to study a possible interaction between NOX2-derived ROS and LDL. Synovial inflammation, cartilage damage and ectopic bone size were assessed on histology. Extracellular ROS production by macrophages was measured in vitro using the Amplex Red assay. Nox2−/− macrophages produced basal levels of ROS but were unable to increase ROS production in response to the alarmin S100A8 or the phorbol ester PMA. Interestingly, Nox2 deficiency reduced cartilage damage, synovial lining thickness and ectopic bone size, whereas these disease parameters were not affected by WD-feeding. These results suggest that NOX2-derived ROS are involved in CiOA development.